Transformation of the system for forming qualified personnel in the digital economy - V. V. Poliakova; M. P. Pochekutov; E. A. Panova (Вестник университета)
At the moment, there is an active digital transformation of the practice and processes in HR management. The use of electronic means, artificial intelligence and information technology can significantly increase the efficiency of HR management. This study presents the concept and various aspects of the use of artificial intelligence in HR management. The purpose of the study is to identify the key aspects of the highly qualified stuff formation in the digital economy. The research method is a comparative and causal analysis of management decisions and steps to prepare and implement the digital HR transformation. As a result of the study, a model of the recruitment process based on artificial intelligence and a map of possible risks were obtained. The results of the study can be useful in the implementation of HR management based on artificial intelligence and information technology.